The Mistress-Slave Dialectic: Paradoxes of Slavery in Three Lxx Narratives - Glancy, Jennifer A. (Journal for the study of the Old Testament, 1996)
This article considers representations of relations between slave-owning women and the women they enslave in three LXX narratives—Susanna, Tobit and Judith. Like other narratives from the ancient Mediterranean world, these narratives perpetuate the attitudes that slave-owners held towards their slaves. The article takes a methodolo gical cue from classical scholars who have attempted 'symptomatic' or 'diagnostic' readings of ancient texts that represent slaves and slavery. In addition, the article examines a narrative written by a former slave in the nineteenth century to highlight the limitations of making assumptions about slaves' attitudes or experiences based on a text written by a slave-owner.